Representation of Human Face, Hands, Clothes in Painting and Pencil Drawing - Ro‘zixon Jalilova (Zien Journals, 2023)
In this article, the role of pencil drawing, easel painting composition in the visual arts of Uzbekistan, the character of the face of the human figure, and the method of depicting the slave are covered.
Keywords: Art College; vocational college; pedagogical universities